Teoria de carteiras e value-at-risk: estudo de caso da CAPEF - Barbosa, Fernanda Aragão (2006)
This work uses the efficient border developed in the scope of the Modern Wallet Theory, objectifying to take care of the peculiarities of the practical sector and to promote a bigger approach with the current ones of finances. In this direction, the prominence is on account of the inclusion of the concept of value-at-risk - VaR as analysis instrument. The verification of the effectiveness of the model will be carried through in such a way of qualitative form, through the quarrel on the traditional efficient wallet and the modified efficient wallet, how much in the quantitative aspect, through the practical application of the model in the Box of Providence of the Employees of the northeast Bank of Brazil - CAPEF, Closed Entity of Complementary Providence sponsored by the northeast Bank, the Box of Medical Assistance of the Employees of the northeast Bank and by the proper CAPEF. Such practical application will allow to inside show the viability of the research of the area of investments of the Pension funds.